CARBON DIOXIDE (CO2) LASER MARKING PROCESS PARAMETER IMPACT ON MARK QUALITY OF POLIVINILCHLORIDE (PVC) MATERIAL - Riekstiņš, Jānis; Sivenkovs, Artūrs; Lazovs, Ļubomirs; Narica, Pāvels (HUMAN. ENVIRONMENT. TECHNOLOGY. Proceedings of the Students International Scientific and Practical Conference, 2017)
Laser technologies nowadays are widely used in material processing. CO2 laser systems in most cases are used in metallic material manufacturing and processing, taking not so big part in processing of plastic materials. This research is dedicated to find advantages or disadvantages and ways to use CO2 laser systems in plastic material processing, by taking PVC material as sample for experiments. PVC plastics is widely used in manufacturing of electrical installation details and devices, it is durable, relatively light, and cheap material. To provide application of various symbols, on the surface of plastic materials, can be used laser systems, which in long term can be more efficient than conventional marking methods. The aim of this work is to find if CO2 laser is appropriate for marking PVC material and to relate the mark quality parameters and the marking process parameters. The research was conducted in the period of time from March 2017 till April 2017, in the Rēzekne Academy of Technology, Physical process and laser technology research center.